The Influence of Digital Literacy, Social Media and E-Commerce Use on Students' Digital Entrepreneurial Intention - Siti Maesaroh; Ratna Kusumawati (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
Digitalization has impacted various sectors, one of which is the world of entrepreneurship. Digitalization brings many positive things to the world of entrepreneurship, including forms of promotion, the creation of job opportunities, and increased productivity in social and economic terms. This study aims to determine the effect of digital literacy, social media, and the use of e-commerce on the digital entrepreneurship intention among students. The sampling method uses the probability sampling technique with the purposive sampling method using formula calculation. This study was conducted on 139 students of the 2020-2022 intake of the Management, Accounting, and Islamic Economics Department, Faculty of Economics and Business, Wahid Hasyim University, Semarang. Research data were obtained from questionnaires and analyzed using multiple linear regression. The results of the hypothesis test show that there is a significant influence between digital literacy, social media, and the use of e-commerce on students' digital entrepreneurship intention. In comparison, the remaining 27.8% is explained by other variables not included in the study.